Lateralized electrodermal dysfunction and complexity in patients with schizophrenia and depression - Bob, Petr; Susta, Marek; Glaslova, Katerina; Pavlat, Josef; Raboch, Jiri (Neuro endocrinology letters, 2007)
OBJECTIVE: Recent evidence indicates that in psychiatric patients with schizophrenia and depression, lateralized EDA changes linked to temporal-limbic electrophysiological dysfunction occur. These clinical findings provide evidence for brain asymmetry and disruptions related to integrative brain activity in pathological conditions. METHODS: These changes in brain asymmetry may be assessed by linear analysis of EDA measurement and nonlinear analysis of brain complexity calculated as information entropy. Two groups of patients with established diagnosis of paranoid schizophrenia (N=35), unipolar depression (N=35) and a control group of 35 healthy controls were examined by measurement of bilateral electrodermal activity (EDA). In non-linear data analysis of the EDA time series in resting state the method of recurrence quantification analysis was applied. RESULTS: In these patients significant right-left EDA asymmetry and asymmetry of information entropy calculated by non-linear recurrence quantification analysis of EDA records have been found. Similar asymmetry has not been observed in the group of healthy controls. CONCLUSIONS: Because information entropy reflects the complexity of the deterministic structure in the system, then unilaterally increased entropy in patients with schizophrenia and depression likely indicates specific nonlinear disturbances in limbic circuits that modulate EDA. These data are in accordance with recent findings that indicate apparent differences in nonlinear neural patterns in the psychiatric diseases and nonlinear behavior of healthy brain.
Keywords: dospělí; funkční lateralita; Female; Nonlinear Dynamics; Functional Laterality; Adult; Electrophysiology; ženské pohlaví; lidé; kůže; schizofrenie; Male; Skin; galvanická kožní odpověď; nelineární dynamika; Schizophrenia; elektrofyziologie; Galvanic Skin Response; deprese; mužské pohlaví; Depression; Humans